Daily Torpor and Sleep in a Non-human Primate, the Gray Mouse Lemur (Microcebus murinus) - Royo, Julie; Aujard, Fabienne; Pifferi, Fabien (Frontiers in Neuroanatomy, 2019)
Daily torpor is an energy-saving process that evolved as an extension of non-rapid eye movement (NREM) sleep mechanisms. In many heterothermic species there is a relation between torpor expression and the repartition of the different behavioral states of sleep. Despite the presence of sleep during this period of hypothermia, torpor induces an accumulation of sleep debt which results in a rebound of sleep in mammals. We aimed to investigate the expression of sleep-wake rhythms and delta waves during daily torpor at various ambient temperatures in a non-human primate model, the gray mouse lemur (Microcebus murinus). Cortical activity was measured with telemetric electroencephalography (EEG) recordings in the prefrontal cortex (PFC) during the torpor episode and the next 24 h following hypothermia. Gray mouse lemurs were divided into two groups: the first group was subjected to normal ambient temperatures (25°C) whereas the second group was placed at lower ambient temperatures (10°C). Contrary to normal ambient temperatures, sleep-wake rhythms were maintained during torpor until body temperature (Tb) of the animals reached 21°C. Below this temperature, NREM and REM sleep strongly decreased or were absent whereas the EEG became isoelectric. The different states of sleep were proportional to Tbmin during prior torpor in contrast to active phases. Delta waves increased after torpor but low Tb did not induce greater delta power compared to higher temperatures. Our results showed that Tb was a determining factor for the quality and quantity of sleep. Low Tb might be inconsistent with the recovery function of sleep. Heterothermy caused a sleep debt thus there was a rebound of sleep at the beginning of euthermia to compensate for the lack of sleep.